Acne vulgaris – comparative analysis of boys and girls - Brudnowski, Dariusz; Ziętkiewicz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Background: Acne vulgaris is a common skin disease affecting almost 100% of young people. It is caused by excessive production of sebaceous glands, keratoses follicularis and inflammation. Aim of the study: The aim of the study was to compare the occurrence, locations, aggravation of symptoms, knowledge about the methods of treatment and the assessment of the problem by girls and boys. Material and methods: We investigated 174 patients: 87 girls and 87 boys at the age between 17 and 20. A questionnaire was composed of 26 questions. The investigations were performed in Poznań high schools. The study material was described according to the percentage of given answers. Conclusions: Our results showed that acne vulgaris occurs later among boys than among girls and some areas such as the neck, the middle of the chest, the back are more often involved. Boys often suffer from chronic and severe varieties of acnes: acne phlegmonosa, conglobata, keloidea and inversa. Boys and girls were treated by the doctor on average in 28% of cases, however boys waited with the decision to go to the doctor longer after the first skin lesions appeared. In the case of boys, the assessment of acne was better but the information about the treatment methods and skin care were mainly less complete.